Fate and biodegradability potential of an emerging micropollutant diclofenac in subsurface environment - Tas, D. O.; Sari, S.; Aydin, E.; Topuz, E.; Pehlivanoglu-Mantas, E. (Springer Science and Business Media LLC, 2017)
The present study deals with the assessment of the fate of an emerging contaminant (diclofenac), present in the subsurface environment at specific concentration levels, and its biodegradation potential under different environmental configurations. Diclofenac is a widely consumed nonsteroidal anti-inflammatory drug used as a painkiller prescribed as pills or ointments and among the most frequently detected pharmaceuticals in wastewater treatment plants’ effluents. Fermentative/methanogenic cultures were enriched from previously contaminated sediment samples. Although partial biodegradation was achieved in all enrichment cultures, complete degradation was not observed. The results reflected that less than 6% of the diclofenac sorbed on the solid phase and the rest was either biotransformed (25–40%) or remained in the liquid phase (55–70%) at the end of 45-day incubation period. Although partial cometabolic degradation of diclofenac occurred in the presence of glucose, biodegradation was not observed in the presence of readily biodegradable carbon source (i.e., acetate). Diclofenac concentration up to 1000 µg/L did not affect the methanogenic activity of the enriched culture. The results of this study will have a significant impact in the designation of the permitted concentration limits of diclofenac before the discharge through wastewater treatment plants.